Bioactive compounds fractionated from endophyte Streptomyces SUK 08 with promising ex-vivo antimalarial activity - Mohamad Zin, Noraziah; Remali, Juwairiah; Nasrom, Mohd Nazir; Ishak, Shafariatul Akma; Baba, Mohd Shukri; Jalil, Juriyati (Elsevier BV, 2017)
Objective: To determine ex vivo antimalarial activity and cytotoxicity of endophytic Streptomyces SUK 08 as well as the main core structure fractionated from its crude extract. Methods: The activities of SUK 08 crude extract were evaluated by using the Plasmodium lactate dehydrogenase assay and synchronization test against rodent malaria parasite Plasmodium berghei, instead of human malarial parasite Plasmodium falciparum. The cytotoxicity of the crude extract was determined by MTT assay. The crude extract was analyzed by thin-layer chromatography and gas chromatography–mass spectrophotometry. Results: The ethyl acetate crude extract showed very promising antimalarial activity with IC50 of 1.25 mg/mL. The synchronization tests showed that ethyl acetate extraction could inhibit all stages of the Plasmodium life cycle, but it was most effective at the Plasmodium ring stage. On the basis of a MTT assay on Chang Liver cells, ethyl acetate and ethanol demonstrated IC50 values of >1.0 mg/mL. The IC50 of parasitemia at 5% and 30% for this extract was lower than chloroquine. Thin-layer chromatography, with 1: 9 ratio of ethyl acetate: hexane, was used to isolate several distinct compounds. Based on gas chromatography–mass spectrophotometry analysis, three core structures were identified as cyclohexane, butyl propyl ester, and 2,3-heptanedione. Structurally, these compounds were similar to currently available antimalarial drugs. Conclusions: The results suggest that compounds isolated from Streptomyces SUK 08 are viable antimalarial drug candidates that require further investigations